Pan-Cancer Analysis of the Mitophagy-Related Protein PINK1 as a Biomarker for the Immunological and Prognostic Role - Zhu, Lizhe; Wu, Wei; Jiang, Siyuan; Yu, Shibo; Yan, Yu; Wang, Ke; He, Jianjun; Ren, Yu; Wang, Bin (Frontiers in Oncology, 2020)
Introduction: The PINK1 gene encodes a serine/threonine protein kinase that localizes to mitochondria and has usually been considered to protect cells from stress-induced mitochondrial dysfunction. PINK1 mutations have been observed to lead to autosomal recessive Parkinson’s disease. However, the immunological and prognostic roles of PINK1 across cancers remain unclear. Material and method: In the current study, we used multiple databases, including Oncomine, PrognoScan, Kaplan-Meier Plotter, GEPIA, TIMER and cBioportal, to investigate the PINK1 expression distribution and its immunological and prognostic role across cancers. Results and discussion: Bioinformatics data revealed that the mRNA expression of PINK1 was downregulated in most tumors. Although there was a significant prognostic value of PINK1 expression across cancers, PINK1 played a protective or detrimental role in different kinds of cancers. liver hepatocellular carcinoma and lung squamous cell carcinoma were selected as representative cancer types for further exploration. We found that PINK1 always played a protective role in liver hepatocellular carcinoma patients in the stratified prognostic analyses of clinicopathological characteristics. There were contradictory results between liver hepatocellular carcinoma and lung squamous cell carcinoma in the correlations of PINK1 expression with immune infiltration, including infiltration of B cells, CD8+ T cells, CD4+ T cells, macrophages, neutrophils and dendritic cells. Furthermore, specific markers of B cells and CD8+ T cells also exhibited different PINK1-related immune infiltration patterns. In addition, there was a significant association between PINK1 copy number variations and immune infiltrates across cancers. Conclusion: The mitophagy-related protein PINK1 can work as a biomarker for prognosis and the immune response across cancers.